2022
DOI: 10.1007/s00787-022-02119-y
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress, coping strategies, and mental health status among adolescents during the COVID-19 pandemic in Switzerland: a longitudinal study

Abstract: This longitudinal, prospective study investigated associations between perceived COVID-19-related stress, coping strategies, and mental health status among adolescents during the first lockdown of the COVID-19 pandemic and one year after the lockdown in Switzerland within a large, national sample. A self-report on-line survey was completed by 553 adolescents (age-range 12–18 years in 2021) in the summers of 2020 and 2021, assessing symptoms of various mental health problems, perceived COVID-19-related stressor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 69 publications
5
12
0
1
Order By: Relevance
“…Given the uniqueness of the COVID-19 pandemic, most studies suggest that the mental health of adolescents has shown a deteriorating trend during the pandemic[ 4 , 5 ]. Other studies have also reported results consistent with the findings of Huang et al [ 1 ], indicating that the incidence of mental disorders among adolescents, such as depression, anxiety, and stress, has decreased during the COVID-19 pandemic[ 6 - 8 ]. However, the mental health status of adolescents remains concerning.…”
Section: To the Editorsupporting
confidence: 80%
“…Given the uniqueness of the COVID-19 pandemic, most studies suggest that the mental health of adolescents has shown a deteriorating trend during the pandemic[ 4 , 5 ]. Other studies have also reported results consistent with the findings of Huang et al [ 1 ], indicating that the incidence of mental disorders among adolescents, such as depression, anxiety, and stress, has decreased during the COVID-19 pandemic[ 6 - 8 ]. However, the mental health status of adolescents remains concerning.…”
Section: To the Editorsupporting
confidence: 80%
“…On the contrary, Voltmer et al [75], examining two points-the year before the COVID-19 pandemic (2019) and the year of the COVID-19 pandemic (2020)-in a study with German university students, did not find significant differences in perceived stress and self-reported symptoms of depression and only a minor elevation in anxiety between 2019 and 2020. Notably, in a longitudinal prospective study [76] during the first lockdown of the COVID-19 pandemic and one year after the lockdown in Switzerland, within a large, national sample of 553 adolescents (age range 12-18 years in 2021), participants reported less COVID-19-related stress one year after the lockdown, and mental health statuses remained stable.…”
Section: Social Support As Key Factor For Mental Healthmentioning
confidence: 99%
“…The impact of COVID-19 will likely last for a long time, and the pandemic has had a tangible and intangible impact on the lives of all citizens, including mental aspects, 29 which must be taken into consideration. Our study found no significant difference in the smoking rate at home, even during the pandemic period, whereas the pet ownership rate decreased at age 18 months and recovered at age 3 years.…”
Section: Discussionmentioning
confidence: 99%